The role of passive avian head stabilization in flapping flight - Pete, Ashley E. (J R Soc Interface, 2015)
Birds improve vision by stabilizing head position relative to their surroundings, while their body is forced up and down during flapping flight. Stabilization is facilitated by compensatory motion of the sophisticated avian head–neck system. While relative head motion has been studied in stationary and walking birds, little is known about how birds accomplish head stabilization during flapping flight. To unravel this, we approximate the avian neck with a linear mass–spring–damper system for vertical displacements, analogous to proven head stabilization models for walking humans. We corroborate the model's dimensionless natural frequency and damping ratios from high-speed video recordings of whooper swans (Cygnus cygnus) flying over a lake. The data show that flap-induced body oscillations can be passively attenuated through the neck. We find that the passive model robustly attenuates large body oscillations, even in response to head mass and gust perturbations. Our proof of principle shows that bird-inspired drones with flapping wings could record better images with a swan-inspired passive camera suspension.